2015
DOI: 10.1007/s40279-015-0419-3
|View full text |Cite
|
Sign up to set email alerts
|

The Transition Period in Soccer: A Window of Opportunity

Abstract: The aim of this paper is to describe the physiological changes that occur during the transition period in soccer players. A secondary aim is to address the issue of utilizing the transition period to lay the foundation for the succeeding season. We reviewed published peer-reviewed studies if they met the following three selection criteria: (1) the studied population comprised adult soccer players (aged >18 years), (2) time points of physiological and performance assessments were provided, and (3) appropriate s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
156
0
14

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(183 citation statements)
references
References 72 publications
7
156
0
14
Order By: Relevance
“…For example, in team sports there are very few situations in the regular annual calendar in which a player can have a prolonged period of complete recovery from specific training and competition demands. Only off-season/transition periods can offer some opportunity for rest [42]. Isolation and the absence of intensive specific training and competition enable both complete cellular recovery and the avoidance of common daily mental stress.…”
Section: Window Of Opportunity During the Isolationmentioning
confidence: 99%
“…For example, in team sports there are very few situations in the regular annual calendar in which a player can have a prolonged period of complete recovery from specific training and competition demands. Only off-season/transition periods can offer some opportunity for rest [42]. Isolation and the absence of intensive specific training and competition enable both complete cellular recovery and the avoidance of common daily mental stress.…”
Section: Window Of Opportunity During the Isolationmentioning
confidence: 99%
“…Despite the growing popularity of women's soccer, no studies were identified that investigate the effect of transition period on the anthropometric and performance parameters. Most published literature available has examined those effects on male [2] rather than female players.…”
Section: Introductionmentioning
confidence: 99%
“…The transition period has been found to elicit moderately negative changes in body composition, sprint performance, and muscle power in male soccer players [2]. Furthermore, decrements in max-imal oxygen consumption (VO2max), time to exhaustion, and intermittent running performance have been reported [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La ausencia de diferencias en el resto de variables en M1 puede ser debida al desentrenamiento durante el período de transición 23 . Según algunos estudios, la desadaptación producida durante el período de vacaciones se traduce en un aumento del porcentaje de grasa corporal, la disminución del rendimiento del sprint con y sin cambio de dirección, el descenso en la potencia muscular y la pérdida de la aptitud aeróbica 24 . Para evitar esta situación en los jugadores y conseguir que se mantengan los niveles óptimos de las capacidades de rendimiento se ha recomendado prescribir una dosis mínima de entrenamiento específico en el plano neuromuscular y cardiovascular 23,24 .…”
Section: Discussionunclassified